(untitled) (Modern education and development, 2025)
The use of interactive resources in teaching English has become an integral part of the educational process today. Along with the development of educational technology, interactive resources provide new opportunities for teachers and students. This article details the importance of interactive resources, types, and how they can be used in teaching English.